Fenomena Influencer Keagamaan Dalam Perubahan Gaya Baragama Anak Muda di Indonesia - Chasadya Baraputra Panditya; Jessica Elizabeth Mukti; Bianca Jillian Kimberly Tendean (Lentera Ilmu Madani, 2025)
The development of digital technology and social media has opened up a new space for the spread of religious values through the presence of religious influencers, especially on the TikTok platform. This research aims to find out how their role affects changes in the religious style of young people in Indonesia. The focus of the research includes communication patterns, the form and content of da'wah content, as well as the response of young audiences to digital religious messages. The approach used is qualitative descriptive through literature studies from 15 scientific journals published in 2020 and above as well as semi-structured interviews with one active influencer and several younger generation audiences. The results show that da'wah through social media presents a more flexible, personal, and contextual way of religion, replacing conservative and institutional approaches. Influencers not only act as preachers, but also as spiritual role models that shape the audience's lifestyle and religious identity. The da'wah approach that is relaxed, visually attractive, and relevant to everyday life makes religious messages easier to accept. Social media is not only an alternative channel for preaching, but also an active space for the younger generation to shape their religious identity in the digital era.